Developing a Data Visualization System for the Bank of America Chicago Marathon (Chicago, Illinois USA). Issue 5 (5th August 2016) - Hanken, Taylor; Young, Sam; Smilowitz, Karen; Chiampas, George; Waskowski, David
Abstract: As one of the largest marathons worldwide, the Bank of America Chicago Marathon (BACCM; Chicago, Illinois USA) accumulates high volumes of data. Race organizers and engaged agencies need the ability to access specific data in real-time. This report details a data visualization system designed for the Chicago Marathon and establishes key principles for event management data visualization. The data visualization system allows for efficient data communication among the organizing agencies of Chicago endurance events. Agencies can observe the progress of the race throughout the day and obtain needed information, such as the number and location of runners on the course and current weather conditions. Implementation of the system can reduce time-consuming, face-to-face interactions between involved agencies by having key data streams in one location, streamlining communications with the purpose of improving race logistics, as well as medical preparedness and response. T Hanken, S Young, K Smilowitz, G Chiampas, D Waskowski .Developing a data visualization system for the Bank of America Chicago Marathon (Chicago, Illinois USA) .Prehosp Disaster Med .2016 ;31 (5 ):572 –577 .